2021
DOI: 10.1021/acs.jpcb.0c10708
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Role of Charged Residue from Transmembrane Domain 5 of Latent Membrane Protein 1 via In Silico Simulations and Wet-Lab Experiments

Abstract: Charged residues are frequently found in the transmembrane segments of membrane proteins, which reside in the hydrophobic bilayer environment. Charged residues are critical for the function of membrane protein. However, studies of their role in protein oligomerization are limited. By taking the fifth transmembrane domain (TMD5) of latent membrane protein 1 from the Epstein–Barr virus as a prototype model, in silico simulations and wet-lab experiments were performed to investigate how the charged states affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The ionizable residue D150 plays a key role in overcoming the entropic penalty to form oligomers, which is consistent with previous studies showing that a single polar residue (Asn, Gln, Asp, and Glu) in the transmembrane segment could mediate the formation of stable trimers by shifting its p K a s in the membrane environment. 30,56 These results also suggest an approach to the design of variants of single-span transmembrane peptide modulators with various potentials to interrupt oligomers in the bilayer.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…The ionizable residue D150 plays a key role in overcoming the entropic penalty to form oligomers, which is consistent with previous studies showing that a single polar residue (Asn, Gln, Asp, and Glu) in the transmembrane segment could mediate the formation of stable trimers by shifting its p K a s in the membrane environment. 30,56 These results also suggest an approach to the design of variants of single-span transmembrane peptide modulators with various potentials to interrupt oligomers in the bilayer.…”
Section: Resultsmentioning
confidence: 82%
“…Previous studies indicated that D150 was the key residue for TMD5 to form a trimeric structure. 25,30 Hence, the conformation of D150 was monitored, and the dihedral of the D150 side chain was measured. At the reaction coordinate of 11.15 Å, all D150s pointed to the center of the trimer (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations